2010
DOI: 10.1038/nchem.586
|View full text |Cite
|
Sign up to set email alerts
|

Million-fold activation of the [Fe2(µ-O)2] diamond core for C–H bond cleavage

Abstract: In biological systems, the cleavage of strong C–H bonds is often carried out by iron centers – such as the methane monooxygenase in methane hydroxylation – through dioxygen activation mechanisms. High valent species with [Fe2(μ-O)2] diamond cores are thought to act as the oxidizing moieties, but the synthesis of complexes that cleave strong C–H bonds efficiently has remained a challenge. We report here the conversion of a synthetic complex with a valence-delocalized [Fe3.5(μ-O)2Fe3.5]3+ diamond core (1) into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
233
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(255 citation statements)
references
References 50 publications
13
233
0
6
Order By: Relevance
“…Recently, an unmasked HS FeðIVÞ ¼ O unit was identified in a valence-localized open core diiron (FeðIIIÞ∕FeðIVÞ) complex (8). The reaction of the C-H bond cleavage by this complex turned out to be approximately 100 times faster than the corresponding mononuclear IS oxo-iron(IV) complex (8). This experimental finding is in accord with the theoretical prediction that quintet ferryl species are more aggressive oxidants than the corresponding triplet counterparts (9,10,11).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Recently, an unmasked HS FeðIVÞ ¼ O unit was identified in a valence-localized open core diiron (FeðIIIÞ∕FeðIVÞ) complex (8). The reaction of the C-H bond cleavage by this complex turned out to be approximately 100 times faster than the corresponding mononuclear IS oxo-iron(IV) complex (8). This experimental finding is in accord with the theoretical prediction that quintet ferryl species are more aggressive oxidants than the corresponding triplet counterparts (9,10,11).…”
supporting
confidence: 79%
“…Presumably because the ðFeOÞ 2þ core is sheltered by the sterically bulky supporting ligand in ½FeðIVÞðOÞ ðTMG 3 trenÞ 2þ , its reactivity toward C-H bond cleavage is only comparable with triplet ferryl analogues (7). Recently, an unmasked HS FeðIVÞ ¼ O unit was identified in a valence-localized open core diiron (FeðIIIÞ∕FeðIVÞ) complex (8). The reaction of the C-H bond cleavage by this complex turned out to be approximately 100 times faster than the corresponding mononuclear IS oxo-iron(IV) complex (8).…”
mentioning
confidence: 99%
“…This is in agreement with the "diamond core" intermediate QS of methane monooxygenase, which has one short (ϳ1.77 Å) and one long (ϳ2.05 Å) Fe--O bond (42). QS can also be viewed as a headto-tail dimer of Fe IV ϭO units (Fe , for which the terminal oxo group is more reactive than the bridging oxo group (43,44). Therefore, we suggest that the terminal oxo group attacks the C2 atom of the phenyl ring.…”
Section: -O-o-fe2supporting
confidence: 61%
“…This has been attributed to strong electron donation from the axial thiolate ligand and explains the high reactivity of the natural thiolate-bound P450-I. Another important finding is the recently demonstrated 73,74 increased reactivity of the linear [(O)Fe IV -O-Fe III (OH 2 )] 2 + model complex, as compared with the ring-like [Fe IV 2 (µ-O) 2 ] 2 + core, that provides evidence for a comparable, more ring-opened form of Q with a terminal Fe IV = O unit as the active species in the reactivity of MMO. Additionally, although direct evidence for the involvement of oxoiron(V) intermediates in water oxidation is lacking in the literature, Kundu et al 97 , has recently demonstrated a O-O bond formation reaction mediated by polynuclear oxoiron(IV) intermediates.…”
Section: Conclusion and Future Challengesmentioning
confidence: 88%
“…Xue et al 71 (Fig. 5c) showed that the terminal iron(IV) oxo units are at least three orders of magnitude more reactive than the ones with diamond cores 74 . The most potent C-H activator is the complex with an S = 2 quintet ground state of the Fe = O moiety.…”
Section: Dinuclear Bis(µ-oxo)diiron(iv) Model Complexesmentioning
confidence: 97%